Treatment options for patients with severe COVID-19 - Morishita, Momoko; Hojo, Masayuki (Global Health & Medicine, 2023)
The coronavirus disease 2019 (COVID-19) pandemic has affected the world for over 3 years. Treatment options have improved substantially during this period, including antiviral drugs, antibody drugs, immune-based agents, and vaccination. While these improvements have reduced mortality rates in patients with COVID-19, some patients still develop severe illness. In this review, we aimed to provide an overview of treatments for patients with severe COVID-19 from study reports and clinical experience. We discussed the treatments from two perspectives: respiratory care and drug treatments. In the respiratory care section, we discussed the usefulness of high-flow nasal cannula therapy and non-invasive ventilation as an alternative to invasive ventilation. In the drug treatments section, we focused on three classes for severe COVID-19 treatment: antiviral drugs, immune-based agents, and anticoagulation therapy. We did not discuss antibody drugs and vaccination, as they are not used for severe COVID-19 treatment.